Changes in Oxidative and Nitrosative Stress Indicators and Vascular Endothelial Growth Factor After Maximum-Intensity Exercise Assessing Aerobic Capacity in Males With Type 1 Diabetes Mellitus - Tota, Łukasz; Matejko, Bartłomiej; Morawska-Tota, Małgorzata; Pilch, Wanda; Mrozińska, Sandra; Pałka, Tomasz; Klupa, Tomasz; Malecki, Maciej T. (Frontiers in Physiology, 2021)
In type 1 diabetes mellitus (T1DM), chronic hyperglycemia causes reactive oxygen and nitrogen species production. Exercise alters the oxidant-antioxidant balance. We evaluated the aerobic capacity and oxidant-antioxidant balance changes after maximum-intensity exercise in T1DM patients. The study involved 30 T1DM subjects and 23 controls. The patients’ average age was 23.4 ± 5.1 years, with a body mass index of 24.3 ± 3.1 kg ∙ m–2 and with satisfactory glycemic control. Among the controls, the respective values equaled 24.7 ± 2.9 years and 22.9 ± 2.1 kg ∙ m–2. Aerobic capacity was assessed with a treadmill test. Peak minute oxygen uptake was significantly lower in T1DM compared with the controls (44.7 ± 5.7 vs. 56.0 ± 7.3 mL ∙ kg–1 ∙ min–1). The total oxidant capacity measured by total oxidative status/total oxidative capacity (TOS/TOC) equaled 321.5 ± 151 µmol ∙ L–1 before and 380.1 ± 153 µmol ∙ L–1 after exercise in T1DM, and 164.1 ± 75 and 216.6 ± 75 µmol ∙ L–1 in the controls (p < 0.05 for all comparisons). A significant difference in the ratio of total antioxidant status/total antioxidant capacity (TAS/TAC) between the groups after the treadmill test was observed (p < 0.05). In conclusion, diabetic patients demonstrated a lower aerobic capacity. The TOS/TOC was significantly higher in T1DM before and after the test.